Synergistic effects of exogenous IAA and melatonin on seed priming and physiological biochemistry of three desert plants in saline-alkali soil - Youwei Zhang; Lei Wang; Xuebo Li; Hao Wen; Xiao Yu; Yixuan Wang (Plant Signaling & Behavior)
To investigate the synergistic effect of IAA and melatonin (MT) on three plants to alleviate the effects of salt damage on plants, we aim to determine the optimal concentrations of exogenous hormone treatments that improve salinity resistance for each species. In this experiment, three desert plants, Sarcozygium xanthoxylon, Nitraria tangutorum, and Ammopiptanthus mongolicus, which are common in Wuhai City, were used as plant materials. Two time periods (12 h,24 h) of exogenous hormone IAA (100 μmol/L) and exogenous melatonin concentration (0, 100, 200, 300 μmol/L) were used to treat the three desert plants in saline soil under different conditions of exogenous IAA and exogenous melatonin. The results indicate that under different concentrations of exogenous IAA and melatonin, the germination rate and vigor of the three desert plant species in saline-alkaline soil improved. However, as the concentration of melatonin increased, the germination rate and vigor of these desert plants were inhibited. Whereas, plant height, root length, leaf length, fresh weight, dry weight, and root vigor of the three desert plants were alleviated under different conditions of exogenous IAA and exogenous melatonin. under the action of two exogenous hormones, the low concentration of melatonin decreased their malondialdehyde content and increased their proline content. As melatonin levels increased, the activity of antioxidant enzymes also rose initially, followed by a subsequent decline. This study highlights the synergistic effects of two exogenous hormones on the critical role of cell osmomodulators and antioxidant enzyme activity in combating salinity damage in three desert plants.